SOLUSI MADRASAH DALAM MENGHADAPI PROBLEMATIKA KETIDAKHADIRAN GURU DALAM KELAS - Hafidurrahman, Moh.; Dannur, Moh.; Sayyi, Ach. (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This paper aims to find solutions and know the reasons for the absence of teachers into the classroom, efforts made madrasah to minimize the absence of teachers. There are some impacts felt by students when teachers are not present in the class, students are harmed and disappointed, this can decrease their interest and motivation to learn. In addition, this affects the discipline of students. The research method used is a theoretical study taken from the opinion of education experts. From this opinion is then analyzed in depth. Absence is also because it is lazy to teach, it can also be a seed of inconsistency for teachers who are usually diligent. Researchers try to find a solution to the problem (problem solving), that madrasah must dare to act so that madrasah is really effective. for example, rewarding teachers who are active and punishment for teachers who rarely attend the classroom, because of some problems in other institutions there is a positive influence on the presence of teachers when there is the application of rewards and punishment to the discipline of teachers who are present in the classroom in teaching and learning activities.